Alkali-Treated Agave Americana Fiber for Reinforcement of Fly Ash-Based Geopolymers - Melanie Rojas; Guido Silva; Javier Nakamatsu; Rafael Aguilar; Suyeon Kim (Journal of Natural Fibers, 2022)
The mechanical properties of Agave americana fibers treated with NaOH solutions (1, 5, and 20 wt.%) for different times (0.5, 1 and 3 h) were investigated. At these conditions, tensile strength and ultimate strain of the fibers were determined. The treatment that required the minimum resources to improve the mechanical performance was 1% NaOH for 1 h. Fiber surface after the alkaline treatment was analyzed by scanning electron microscopy (SEM); it showed partial remotion of impurities at the mildest condition (1% NaOH for 0.5 h) and an apparent surface decomposition when using the most harsh condition (20% NaOH for 3 h). Fly ash-based geopolymer composites with different treated fiber contents were prepared. The compressive, flexural, and splitting tensile strengths of the composite geopolymers at seven days of age were determined. Results indicated that the addition of fibers slightly influenced the compressive strength; however, the ductility capacity was improved by up to 26% when 1% of treated fiber was incorporated. Regarding the tensile behavior, results indicate a direct relationship of strength with the amount of fibers, up to 36% improvement with 1% fiber content. Morphological of the fiber-reinforced geopolymer matrices was finally studied by SEM.